Platelet-Related Indicators: Potential Role in Early Prediction of Bronchopulmonary Dysplasia - Xixi Zhang; Cuie Chen; Changwei Chen; Shujun Chen; Ningjie Lu; Jing Zhang; Yuanyuan Sun (Clinical and Experimental Obstetrics & Gynecology)
Background: Bronchopulmonary dysplasia (BPD) is the most common chronic respiratory disease in extreme preterm infants, and inflammation is the main contributor that initiates this lung injury. As platelet-related indicators such as platelet-to-lymphocyte ratio (PLR) and platelet-to-neutrophil ratio (PNR) are potential systemic inflammatory biomarkers and it has been shown to be good predictors of lung diseases. The objective of this study was to assess the potential role of platelet-related indicators in early prediction for BPD. Methods: Neonates with gestational ages <32 weeks (w) from two tertiary neonatal intensive care units between January 2019 and April 2022 were included and the association between the platelet-related indicators and BPD were analyzed by logistic regression analysis and receiver operating characteristic curve. Results: 533 preterm infants were admitted, including 165 preterm infants with BPD and 368 preterm infants without BPD. The infants in the BPD group had higher PLR and PNR at birth, lower platelet (P) count at 2 w than those in the without BPD group. The high PLR at birth, high PNR at birth and low P at 2 w were independently associated with the risk of BPD. PLR at birth represented a predictive value for BPD with the area under the curve (AUC) being 0.589, sensitivity was 0.661, and specificity was 0.579 when the threshold was 135.33. PNR at birth represented a predictive value for BPD with the AUC being 0.576, sensitivity was 0.612, and specificity was 0.589 when the threshold was 129.12. P at 2 w represented a predictive value for BPD with the AUC being 0.668, sensitivity was 0.548, and specificity was 0.711 when the threshold was 285.5. The predictive value of the model was improved when including PLR at birth, PNR at birth, P at 2 w, and gestational age, with AUC being 0.798, sensitivity was 0.754, and specificity was 0.737. Conclusions: Combining PLR at birth, PNR at birth, P at 2 w, and gestational age improved the value in early prediction of BPD.